Recurrent acute otitis media detracts from health-related quality of life. Issue 2 (11th January 2017) - Kujala, T; Alho, O-P; Kristo, A; Uhari, M; Renko, M; Pokka, T; Koivunen, P
Abstract: Objective: Acute otitis media causes discomfort to children and inconvenience to their parents. This study evaluated the quality of life in children with recurrent acute otitis media aged less than 24 months. Methods: Quality of life was evaluated in 149 children aged 10 to 24 months who were referred to the Oulu University Hospital on account of recurrent acute otitis media. The children were treated with or without surgery. Age-matched controls were selected randomly from the general child population. Parents completed the Child Health Questionnaire. Results: The children with recurrent acute otitis media had a significantly poorer quality of life than control children. The control children with a history of a few acute otitis media episodes had a significantly poorer quality of life than those without any such history. The quality of life of the children with recurrent acute otitis media improved during the one-year follow up, regardless of the treatment, but did not reach the same level as healthy children. Conclusion: Acute otitis media detracted from quality of life when a generic measure was used. The mode of treatment used to prevent further recurrences of acute otitis media did not influence quality of life improvement.